INCREASING MOTIVATION IN THE LEARNING PROCESS AND ENCOURAGING STUDENTS TO ACTIVELY PARTICIPATE IN LESSONS (Лучшие интеллектуальные исследования, 2024)
Abstract: This article discusses strategies to increase motivation within the learning process and to encourage students to actively participate in lessons. Methods such as adopting a personalized approach, employing engaging and modern techniques, utilizing praise and encouragement, and promoting a feedback and reflection system are effective for enhancing motivation. Meanwhile, strategies like group work, stimulating discussions and question-answer sessions, organizing interactive games, and focusing on individual engagement are useful for fostering active participation in lessons.